Determination of decay resistance against Pleurotus ostreatus and Coniophora puteana fungus of heat-treated scotch pine, oak and beech wood species - Umit Ayata; Caglar Akcay; Bruno Esteves (Maderas: Ciencia y Tecnología, 2017)
The objective of this study, to investigate decay resistance against Pleurotus ostreatus and Coniophora puteana fungus of heat-treated (ThermoWood method) Scotch pine, oak and beech wood species. Scotch pine (Pinus sylvestris), oak (Quercus petreae) and beech (Fagus orientalis) wood species were heat treated at 190°C for 2 h, 212°C for 1 h and 2 h by the ThermoWood® method. Untreated and heat-treated specimens were exposed to white-rot fungus (Pleurotus ostreatus) and brown-rot fungus (Coniophora puteana) for 12 weeks according to procedures defined in JIS K 1571 standard. After weight losses of all specimens were calculated. According to the results, least weight loss was determined on heat treated at 212°C for 2 h. Heat treatment can be used effectively against fungal attack for Scotch pine, oak and beech wood species.